Menanamkan Jiwa Kewirausahaan Melalui Pelatihan Pembuatan Kerajinan Decoupage: Pendampingan Ibu-Ibu Persatuan Istri Karyawan - Suhartini Suhartini; Handy Gibran Pratama (Komunitas Dosen Indonesia, 2022)
This assistance aims to improve economic capacity and skills for housewives during the Covid-19 pandemic. The Covid-19 pandemic has had a devastating impact on society. Now the community is limited to carrying out activities in public areas due to the spread of the virus through community mobility, for that all activities are focused on their respective residences. For housewives, there is not much that can be done at home other than taking care of the family. There is a lot of free time that can be utilized for useful things, such as developing skills. In addition, from skills can also be used as a way to find additional income, because the current pandemic period is a time of uncertainty, it is important for every person to prepare themselves with skills and alternatives to income. For this reason, researchers took the initiative to organize mentoring through decoupage craft training to instill an entrepreneurial spirit and earn additional income, and in order to empower women to be independent, and creative in the pandemic period. Decoupage is a craft that originated in France. This craft is in accordance with environmental campaigns that recycle, this craft can utilize unused items such as magazines, newspapers into decoupage craft materials. Implementation is carried out offline by paying attention to health protocols that have been vaccinated as much as 2 (two) doses.